1996
DOI: 10.1093/clinids/22.6.1057
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococcal Pleural Empyemas in Children

Abstract: Empyema rarely complicates pneumonia. In a 361-bed regional pediatric hospital, 50 pleural empyemas were identified from 1988 through 1994; 17 (34%) occurred in the last 12 months of this period, for which the incidence was 3.3 per 100,000 of the population aged < or = 18 years (P < .05, chi 2 test). A significant seasonal prevalence was observed: 50% of cases occurred in the winter (P < .001, chi 2 test). In contrast with the findings of previous studies, in which empyemas predominantly occurred in infants, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
1
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(71 citation statements)
references
References 30 publications
6
63
1
1
Order By: Relevance
“…Empyema, as a complication of pneumonia, was defined according to several major and minor criteria (21). The major criteria were the presence of pus in the pleural space, the need for surgical decortication, and the positivity of a pleural fluid culture.…”
Section: Patientsmentioning
confidence: 99%
“…Empyema, as a complication of pneumonia, was defined according to several major and minor criteria (21). The major criteria were the presence of pus in the pleural space, the need for surgical decortication, and the positivity of a pleural fluid culture.…”
Section: Patientsmentioning
confidence: 99%
“…Streptococcus pneumoniae serotype 1 is not a commonly recovered pneumococcal serotype among children with invasive or local respiratory disease in the United States and is not included in the 7-valent pneumococcal conjugate vaccine (6,7). Several investigators have documented an increase in invasive disease caused by S. pneumoniae capsular serotype 1 in selected populations in North America (3,5,14).…”
mentioning
confidence: 99%
“…5 et al (51.81%), William et al 6 pyogenic (40%). Our study has shown TB as the most common origin, i.e.…”
Section: Discussionmentioning
confidence: 96%